Microbial extraction of biotin from lignocellulose biomass and its application on glutamic acid production. (September 2019) - Han, Xushen; Li, Li; Bao, Jie
Graphical abstract: Highlights: Microbial extraction of biotin from lignocellulose hydrolysate was first conducted. Large amounts of biotin in corn leaves were well preserved in acid pretreatment. Corynebacterium glutamicum showed a strong ability of biotin uptake. Overexpression of the bioYMN gene cluster strengthened biotin uptake capacity. The novel biotin-rich cell extract facilitated glutamic acid fermentation. Abstract: Biotin (vitamin B7 ) is an important nutrient for various fermentations. It is abundant in agricultural lignocellulose biomass and maintains stable in biorefinery processing chain including acid pretreatment, biodetoxification and saccharification. Here we show a microbial extraction of biotin from biotin-rich corn leaves hydrolysate. Corynebacterium glutamicum was found to have the highest biotin uptake capacity among different biotin auxotrophic microorganisms, and it was further significantly increased by overexpressing the bioYMN gene cluster encoding biotin transporter. Finally 250 folds greater biotin was extracted by recombinant C. glutamicum (303.8 mg/kg dry cell) from virgin corn leaves (1.2 mg/kg), which was far higher than that in commonly used fermentation additives including yeast extract (∼2 mg/kg), molasses (∼1 mg/kg) and corn steep liquor (∼0.75 mg/kg). The biotin extracted from corn leaves was successfully applied to glutamic acid fermentation. This is the first report on microbial extraction of biotin from lignocellulose biomass and fermentation promotion application.